Kinetics of Thermal Decomposition of Carbon Nanotubes Decorated with Magnetite Nanoparticles - Rubén H. Olcay; Elia G. Palacios; Iván A. Reyes; Laura García-Hernández; Pedro A. Ramírez-Ortega; Sayra Ordoñez; Julio C. Juárez; Martín Reyes; Juan-Carlos González-Islas; Mizraim U. Flores (C)
Magnetite nanoparticles were synthesized using the green chemistry technique; ferric chloride was used as a precursor agent and Moringa oleifera extract was used as a stabilizer agent. A black powder, characteristic of magnetite, was obtained. X-ray diffraction was performed on the synthesis product and identified as magnetite (Fe3O4). Scanning electron microscopy characterization shows that nanoparticles have a spherical morphology, with sizes ranging from 15 nm to 35 nm. The synthesis of carbon nanotubes was carried out by the pyrolytic chemical deposition technique, from which multiwalled carbon nanotubes were obtained with diameters of 15–35 nm and of varied length. The decoration was carried out using the wet and sonification technique, where a non-homogeneous coating was obtained around the nanotubes. The thermal decomposition for both decorated and undecorated nanotubes presents two mass losses but with different slopes, where the activation energy for the decorated carbon nanotubes was 79.54 kJ/mol, which shows that the decoration gives more stability to the nanotubes since the activation energy of the undecorated nanotubes is 25.74 kJ/mol.